Aspectos Fisiológicos Talinum fruticosum (L.) Juss. em diferentes regimes hídricos. - Santos, Robson de Jesus (2022)
Talinum fruticosum (L.) Juss. is an unconventional food plant that occurs in the semiarid, with high protein content and medicinal properties. However, the region is marked by water deficit, demanding regulatory mechanisms in the plants. Thus, the objective of this work was to evaluate the impact of water deficit on the physiological aspects of T. fruticosum. Plants were subjected to water deficit treatments that derived from the maximum water holding capacity of the soil and corresponded to 0, 20, 40, 60, 80 and 100% of field capacity (FC), irrigation occurred at seven days intervals. At 21 days, after imposition of the treatments, the centesimal composition, water relations, gas exchange, as well as biochemical, enzymatic and morphological aspects were evaluated, however, enzymes were evaluated in 3 periods 0, 14 and 21 days. Water deficit was found to influence the energy content allocation of leaf dry biomass, water relations and gas exchange of plants, with limitation for carbon gain. Promoting biochemical adjustments were the compatible solutes, proteins, sugars, and amino acids. The enzymatic activity of SOD, APX and CAT was influenced by water deficit, with an increase in APX and CAT enzymes up to 14 days of water deficit and decrease with prolonged deficit. The morphological aspects showed a decrease with increasing water restriction. Thus, the limitation of the water resource in the soil implies changes in the physiological aspects of T. fruticosum, and distinct mechanisms are used to maintain the species under temporary drought conditions.